Pemanfaatan Kahoot! dalam Meningkatkan Motivasi dan Hasil Belajar Materi Aturan Penggunaan Tanda Baca pada Siswa Sekolah Menengah Atas - Mochammad Afwan Muchlisin (Lingua Franca, 2026)
This study aims to examine the effectiveness of using the gamification platform Kahoot! in improving students’ learning outcomes on punctuation usage rules. An embedded mixed-methods design was employed in this study. A total of 10 twelfth-grade students from SMA Darul Ulum Driyorejo were selected as participants from the overall population of 30 students. A learning outcomes test administered both before and after the treatment served as the research instrument. Pre-test and post-test scores from ten twelfth-grade students constituted the main quantitative data in this study. The quantitative data were analyzed descriptively by comparing students’ scores before and after the treatment. In contrast, the questionnaire data were analyzed using a descriptive-interpretive approach. The results indicated that all students improved their learning outcomes, as demonstrated by higher post-test scores than pre-test scores. In addition, the questionnaire analysis revealed positive student responses toward the use of Kahoot! the students reported increased motivation, greater participation, healthy competition, and a more interactive and enjoyable learning atmosphere. These findings suggest that the use of Kahoot! shows effectiveness in promoting students’ academic attainment and motivation in learning punctuation usage rules.